From an idealized separation of powers to its practical problems in the Rule of Law - Cichelero, César Augusto; Ferri, Caroline; Nunes, Eduardo Brandão (Revista de Investigações Constitucionais, 2018)
The paper presents the Separation of Powers as a principle. It means that it is one of several possible political choices. We take this conception and then we aim to explain how it develops with relevance in a Rule of Law and its procedures. It was analytically perceived that such conception is idealized because it fails to address practical problems. The main problematic confronted is in relation to the activity of the Judiciary, exemplified through Brazilian conflicts between the different powers, in this paper we approach, for this purpose, the vaquejada case. In order to try to overcome such problems, the presented hypothesis is that a dialogic theory can provide some answers by promoting dialogue through equilibrium and partnership between the powers and citizens.